Teach As He Taught - Sigiro, Adi Suhenra (Sekolah Tinggi Teologi Hagiasmos Mission, 2024)
After reading this book, the author understands that a Christian Religious Education teacher in both school and church contexts, who wants to teach must have thorough preparation, such as living in the knowledge of God, understanding the Bible and the basics of teaching the Christian faith, and having good character. endure the test, have intimate fellowship with God. Apart from being spiritual, the preparation of a Christian Religious Education teacher also includes the following, namely, before teaching, a Christian Religious Education teacher must also be able to formulate learning objectives, and even prepare learning through groups. The next part that a Christian Religious Education teacher must prepare is to prepare the curriculum or teaching materials in class. To help in teaching, a Christian Religious Education teacher must master and improve his teaching skills. Christian Religious Education Teachers must also be able to use various approaches through stories, lectures, sermons and various illustrations to help students understand the lesson messages conveyed by the teacher. A Christian Religious Education teacher must also be intelligent in managing the learning class. The room must be arranged in such a way that students are enthusiastic about participating in learning. Furthermore, a successful Christian Religious Education teacher will be successful if, through learning, students have an attitude of love and obedience to God. Because their goal in participating in learning is to become disciples for the Lord Jesus. Therefore, in teaching a Christian Religious Education teacher must be able to first provide examples or role models for students so that students have an idea of ​​the behavior that must be imitated as disciples of Christ. A professional Christian Religious Education teacher must have true commitment and uphold the values ​​of the truth of God's word which are the basis for his life.